Acceptance and commitment training to promote psychological flexibility in ice hockey performance: A controlled group feasibility study - Lundgren, T.; Reinebo, G.; Näslund, M.; Parling, T. (Journal of Clinical Sport Psychology, 2020)
Despite the growing popularity of mindfulness and acceptance-based performance enhancement methods in applied sport psychology, evidence for their efficacy is scarce. The purpose of the current study is to test the feasibility and effect of a psychological training program based on Acceptance and Commitment Training (ACT) developed for ice hockey players. A controlled group feasibility designed study was conducted and included 21 elite male ice hockey players. The ACT program consisted of four, once a week, sessions with homework assignments between sessions. The results showed significant increase in psychological flexibility for the players in the training group. The outcome was positive for all feasibility measures. Participants found the psychological training program important to them as ice hockey players and helpful in their ice hockey development. Desirably, future studies should include objective performance data as outcome measure to foster more valid evidence for performance enhancement methods in applied sport psychology.